GENERAL-METHOD FOR REDUCING THE 2-BODY DIRAC-EQUATION - Galeao, A. P.; Ferreira, P. L. (American Institute of Physics (AIP), 1992)
A semirelativistic two-body Dirac equation with an enlarged set of phenomenological potentials, including Breit-type terms, is investigated for the general case of unequal masses. Solutions corresponding to definite total angular momentum and parity are shown to fall into two classes, each one being obtained by solving a system of four coupled first-order radial differential equations. The reduction of each of these systems to a pair of coupled Schrodinger-type equations is also discussed.